2008
DOI: 10.1016/j.dam.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Identities via Bell matrix and Fibonacci matrix

Abstract: In this paper, we study the relations between the Bell matrix and the Fibonacci matrix, which provide a unified approach to some lower triangular matrices, such as the Stirling matrices of both kinds, the Lah matrix, and the generalized Pascal matrix. To make the results more general, the discussion is also extended to the generalized Fibonacci numbers and the corresponding matrix. Moreover, based on the matrix representations, various identities are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…olacak şekilde = ( ) ve = ( ) matrisleri tanımlanır (Wang, 2008). şeklinde çarpanlarına ayrılabilir (Wang,2008).…”
Section: Fibonacci Matrisi Ve Bell Matrisi Arasındaki öZdeşliklerunclassified
“…olacak şekilde = ( ) ve = ( ) matrisleri tanımlanır (Wang, 2008). şeklinde çarpanlarına ayrılabilir (Wang,2008).…”
Section: Fibonacci Matrisi Ve Bell Matrisi Arasındaki öZdeşliklerunclassified
“…Recently the Riordan group has been used to obtain sequence identities. For example, in [7] the authors rewrote a combinatorially interesting element (g, f ) ∈ R by a product of two elements to obtain sequence identities.…”
Section: The Riordan Groupmentioning
confidence: 99%
“…Various properties of these matrices and their generalizations have been studied, e.g. [1,2,6]. Another interesting connection is given in [3], where it is shown that the maximal determinant of an n × n (0,1)-Hessenberg matrix is F n .…”
Section: Introductionmentioning
confidence: 99%